Porous Transparent Conductors: Nanostructured Antimony‐Doped Tin Oxide Layers with Tunable Pore Architectures as Versatile Transparent Current Collectors for Biophotovoltaics (Adv. Funct. Mater. 37/2016). (4th October 2016) - Peters, Kristina; Lokupitiya, Hasala N.; Sarauli, David; Labs, Mathias; Pribil, Mathias; Rathouský, Jiří; Kuhn, Alexander; Leister, Dario; Stefik, Morgan; Fattakhova‐Rohlfing, Dina
Abstract : On page 6682, D. Leister, M. Stefik, D. Fattakhova‐Rohlfing, and co‐workers describe the fabrication of nanostructured transparent electrodes with remarkably tunable morphologies and adjustable pore sizes from 10–80 nm. Porous conducting scaffolds integrate high amounts of photoactive photosystem proteins. This results in greatly increased photocurrents, making them versatile current collectors for the development of bioelectronic devices. Cover image designed by Christoph Hohmann, Nanosystems Initiative Munich (NIM).